Comparison of Transit-Oriented Development (TOD) Implementation in Malaysia and Indonesia: Policy Analysis and Implications for Sustainable Urban Planning - degdo suprayitno; Sungkono Sungkono; Wahyuddin Latunreng (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
Transit-Oriented Development (TOD) is an urban development strategy that integrates public transport systems with land-use planning to promote sustainable mobility and reduce reliance on private vehicles. Malaysia has implemented TOD since the early 2000s through projects such as KL Sentral and Tun Razak Exchange, whereas Indonesia began systematic implementation in 2019 with the operation of MRT Jakarta. This study aims to compare TOD implementation in both countries, identify key enabling factors and constraints, and formulate policy recommendations to strengthen sustainable urban planning. Using a qualitative literature-review approach, the research analyzes national policy coherence, multimodal transport integration, private-sector involvement, and socio-economic impacts. The findings show that Malaysia has achieved a more mature TOD ecosystem supported by consistent national policies, strong multimodal connectivity, and significant participation from private developers. In contrast, Indonesia continues to face fragmented regulations, spatial-planning challenges, and housing affordability issues that hinder TOD optimization. The study concludes that Indonesia can benefit from Malaysia’s experience by strengthening national TOD regulations, improving cross-agency coordination, enhancing land-value capture mechanisms, and expanding affordable housing provision to ensure inclusive and sustainable TOD development.